2020
DOI: 10.3390/en13143648
|View full text |Cite
|
Sign up to set email alerts
|

Consortium Growth of Filamentous Fungi and Microalgae: Evaluation of Different Cultivation Strategies to Optimize Cell Harvesting and Lipid Accumulation

Abstract: This study aims to evaluate the potential of consortium biomass formation between Mucor circinelloides, an oleaginous filamentous fungal species, and Chlorella vulgaris, in order to promote a straightforward approach to harvest microalgal cells and to evaluate the lipid production in the consortium system. A synthetic medium with glucose (2 g·L−1) and mineral nutrients essential for both fungi and algae was selected. Four different inoculation strategies were assessed, considering the effect of simultaneous vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…For example, Rajendran and Hu (2016) tested attachment of Chlorella vulgaris cells with Mucor circinelloides and Mucor hiemalis on a polymer-cotton composite matrix, and after 8 days 99% of Chlorella vulgaris biomass was aggregated in the form of biofilm. Similar results were obtained in a study by Zorn et al (2020). The co-culture of Mucoromycota and microalgae is a new biomass production process that has direct applications in wastewater treatment and bioremediation.…”
Section: Co-culturing Mucoromycota With Algae As a Novel Process For ...supporting
confidence: 86%
See 1 more Smart Citation
“…For example, Rajendran and Hu (2016) tested attachment of Chlorella vulgaris cells with Mucor circinelloides and Mucor hiemalis on a polymer-cotton composite matrix, and after 8 days 99% of Chlorella vulgaris biomass was aggregated in the form of biofilm. Similar results were obtained in a study by Zorn et al (2020). The co-culture of Mucoromycota and microalgae is a new biomass production process that has direct applications in wastewater treatment and bioremediation.…”
Section: Co-culturing Mucoromycota With Algae As a Novel Process For ...supporting
confidence: 86%
“…For example, Cunninghamella echinulata can efficiently agglomerate with cells of the microalgae Scenedesmus obliquus to harvest up to 92.7% of the cells and improve biomass and lipid yield by 2.24 and 1.49-folds respectively (Srinuanpan et al 2018). The increase in lipid content can be explained by the competition of microalgae and fungi for nitrogen, which leads to a higher accumulation of lipids for both (Zorn et al 2020). However, it has been shown that pelletization of microalgae by Mucoromycota appears to be strain-specific, and that not all Mucoromycota species are capable to pelletize microalgae (Gultom and Hu 2013;Srinuanpan et al 2018).…”
Section: Co-culturing Mucoromycota With Algae As a Novel Process For ...mentioning
confidence: 99%
“…For example, in the co-culture of Chlorella and Aspergillus, microalgae biomass yield, lipid content, and cellular oil exhibited improvements ( Yang et al, 2019 ). Similarly, the consortium of Mucor circinelloides and C. vulgaris showed improved biomass yield, lipids, and saturated and unsaturated fatty acids that can be utilized for biodiesel production ( Zorn et al, 2020 ). However, the effectiveness of this method significantly depends on the selection of microorganisms and their interactions.…”
Section: Microalgae Fungi Co-cultivationmentioning
confidence: 99%
“…Zorn et al [7] investigated the consortium between oleaginous filamentous fungal species Mucor circinelloides and microalga Chlorella vulgaris to promote biomass harvesting and to evaluate lipid production through four different inoculation strategies. Using a mature fungal mycelium with high microalgal cell concentration, biomass samples with up to 79% of the dry weight as algae and recovery rates greater than 97% were achieved.…”
Section: Contributions To This Special Issuementioning
confidence: 99%